Improving Mental Activities by Using Project Based Learning Model for Elementary School Students - Abna Hidayati (Peneliti.net, 2023)
Project-based learning (PjBL) provides opportunities for students to be able to improve their learning activities. The objective of study is to investigate the use of PjBL in improving students' mental activity. The methodology used in this study is quantitative with quasy experiment. The sample was taken purposively by involving 40 elementary school students of grade IV. The research instrument is an activity sheet. Student activity was observed by observers consisting of two teachers who were present during the lesson using student activity observation sheets. Student activity observation sheets are made based on indicators of learning activities. The questionnaire was tested for validity and practicality. The results showed that the research hypothesis was accepted that learning with PjBL which was carried out in the experimental class was significantly different from the experimental class. The resulting tcount is 2.4130 . While the ttable obtained is 2.0244. Because tcount is greater than ttable, the hypothesis is accepted. Based on the results of the study it was concluded that teachers need to design learning activities especially those that involve students' mental processes.